Land degradation neutrality: a pathway to achieving sustainable development goals and ecosystem resilience - Sukhendu Nandi; Soumyadeep Das; Subrata Gorain; Suman Dutta; Malini Roy Choudhury; Sumanta Das (Discover Soil)
Abstract Land degradation poses a significant global threat, undermining ecosystems, food security, and livelihoods. As a response, land degradation neutrality (LDN) has emerged as a pivotal strategy within the framework of Sustainable Development Goal (SDG) 15.3, aiming to halt and reverse land degradation by 2030. Despite its significance, achieving LDN remains a complex challenge due to financial limitations, fragmented policies, and inadequate monitoring mechanisms. This review critically examines LDN’s role in fostering sustainable development and ecosystem resilience by balancing land degradation with restoration through practices such as agroforestry, conservation agriculture, and ecosystem-based management. The study identifies key research gaps, including the need for innovative financing strategies, integrated policy frameworks, and effective monitoring tools to track LDN progress. Our analysis highlights the socio-economic and environmental co-benefits of LDN, such as enhanced agricultural productivity, improved biodiversity, and strengthened climate resilience through carbon sequestration. Methodologically, the paper synthesizes global and regional case studies, offering insights into successful LDN strategies and their scalability. The findings underscore that achieving LDN by 2030 requires coordinated global collaboration, policy coherence, and inclusive stakeholder engagement. Overall, this review positions LDN as a crucial pathway for combating desertification, ensuring food security, and building climate-resilient ecosystems, reinforcing its integral role in advancing global sustainability efforts. Graphical abstract